Nondispersive Infrared Photometer Based on a Rotating Interference Filter for Investigation of Climacteric Fruit Ripening. (2016) - Eberhardt, André; Schmitt, Katrin; Rademacher, Sven; Huber, Jochen; Bauersfeld, Marie-Luise; Wöllenstein, Jürgen
Abstract: In the supply chain of perishable goods, like fruits and vegetables, the measurement of ethylene is important to ensure constant high quality and prevent fast maturation and decay. Ethylene sensors must therefore be sensitive down to the ppb-range, reliable, robust and cheap enough for the use inside a container or storage location. We present a self-referencing single channel nondispersive infrared photometer with focus on system stability for measurement of the ethylene content at 10.53 μm. The self-referencing is achieved using a rotating narrow-band interference filter swept across the v 7 absorption band. This allows the determination of a baseline for referencing. With our laboratory setup, we could show the proof-of-principle and a good agreement with simulations. A detection limit of 50 ppm was achieved with an optical path of 124.8 cm. Based on these results, simulations showed that resolutions down to ppb-range can be achieved with an improved optical long path cell and optimized integrated electronics for signal noise reduction.